2016
DOI: 10.1515/ngoe-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Performance of Cubic Splines and Nelson-Siegel Model for Estimating the Zero-coupon Yield Curve

Abstract: Understanding the relationship between interest rates and term to maturity of securities is a prerequisite for developing financial theory and evaluating whether it holds up in the real world; therefore, such an understanding lies at the heart of monetary and financial economics. Accurately fitting the term structure of interest rates is the backbone of a smoothly functioning financial market, which is why the testing of various models for estimating and predicting the term structure of interest rates is an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This approach has continued to enjoy wider acceptance in the recent empirical literature (see, e.g. Zhu et al, 2019;Jiang et al, 2019;Lorenčič, 2016;Kim et al, 2019;Noor et al, 2014). Interpolation procedures have vastly been employed in time series and cross-sectional data sets (Honaker & King, 2010;Lepot et al, 2017;Wongsai et al, 2017), and predominantly in groundwater resource data mappings due to challenges of data limitations associated with empirical analysis in this subject area.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has continued to enjoy wider acceptance in the recent empirical literature (see, e.g. Zhu et al, 2019;Jiang et al, 2019;Lorenčič, 2016;Kim et al, 2019;Noor et al, 2014). Interpolation procedures have vastly been employed in time series and cross-sectional data sets (Honaker & King, 2010;Lepot et al, 2017;Wongsai et al, 2017), and predominantly in groundwater resource data mappings due to challenges of data limitations associated with empirical analysis in this subject area.…”
Section: Methodsmentioning
confidence: 99%
“…(Peck, 2017, 2) It studies the changing patterns of the industrialisation of Maribor, focusing especially on the 1980s and 1990s when the most significant restructuring occurred. Various scholars already discussed the (de)industrialisation of the Maribor region (Lorber, 2006b;Lorenčič, 2010;Slavec, 1995). We complement the existing studies by putting Maribor´s industrialisation dynamics into a broader socio-historical context.…”
Section: Ključne Besedementioning
confidence: 99%
“…Hattori and Miyake (2016) observed that the B-Spline method produced better yield estimates for municipal bonds when compared with the Svensson model. Lorenčič (2016) empirically contrasted the performance of spline based method with the parametric methods in the estimation of Austrian government bonds. Our method improves the putative B-Spline method by automatically selecting the location of the segments and introducing shape constraints on the yield curve.…”
Section: Related Workmentioning
confidence: 99%